Hidden myelodysplastic syndrome (MDS): A prospective study to confirm or exclude MDS in patients with anemia of uncertain etiology. (5th October 2018) - Bastida, José María; López‐Godino, Oriana; Vicente‐Sánchez, Ana; Bonanad‐Boix, Santiago; Xicoy‐Cirici, Blanca; Hernández‐Sánchez, Jesus M.; Such, Esperanza; Cervera, Jose; Caballero‐Berrocal, Juan C.; López‐Cadenas, Félix; Arnao‐Herráiz, Mario; Rodríguez, Inés; et al.
Abstract: Introduction: Diagnosis of myelodysplastic syndromes (MDSs) when anemia is the only abnormality can be complicated. The aim of our study was to investigate the primary causes of anemia and/or macrocytosis of uncertain etiology. Methods: We conducted a multicenter, prospective study over 4 months in three hematology laboratories. In step 1, we used an automated informatics system to screen 137 453 hemograms for cases of anemia and/or macrocytosis (n = 2702). In step 2, we excluded all patients whose anemia appeared to be due to a known cause. This left 290 patients had anemia of uncertain etiology. In step 3, we conducted further investigations, including a peripheral blood smear, and analysis of iron, vitamin B12, folate, and thyroid hormone levels. Results: A differential diagnosis was obtained in 139 patients (48%). The primary causes of anemia were iron deficiency (n = 59) and megaloblastic anemia (n = 39). In total, 25 hematologic disorders were diagnosed, including 14 patients with MDS (56%). The median age of MDS patients was 80 years, 12 had anemia as an isolated cytopenia, and most (n = 10) had lower‐risk disease (IPSS‐R ≤ 3.5). SF3B1 mutations were most frequent (n = 6) and correlated with the presence of ring sideroblasts (100%) and associated with better prognosis ( P  =   0.001). Conclusions: Our prospective, four‐step approach is an efficient and logical strategy to facilitate the diagnosis of MDS on the basis of unexplained anemia and/or macrocytosis, and may allow the early diagnosis of the most serious causes of anemia. Molecular analysis of genes related to MDS could be a promising diagnostic and prognostic approach.